Ejaculate investment and attractiveness in the stalk‐eyed fly, Diasemopsis meigenii. Issue 6 (18th April 2013) - Harley, Elisabeth; Birge, Leanna M.; Small, Jennifer; Tazzyman, Samuel J.; Pomiankowski, Andrew; Fowler, Kevin
Abstract The phenotype‐linked fertility hypothesis proposes that male fertility is advertised via phenotypic signals, explaining female preference for highly sexually ornamented males. An alternative view is that highly attractive males constrain their ejaculate allocation per mating so as to participate in a greater number of matings. Males are also expected to bias their ejaculate allocation to the most fecund females. We test these hypotheses in the African stalk‐eyed fly, Diasemopsis meigenii. We ask how male ejaculate allocation strategy is influenced by male eyespan and female size. Despite large eyespan males having larger internal reproductive organs, we found no association between male eyespan and spermatophore size or sperm number, lending no support to the phenotype‐linked fertility hypothesis. However, males mated for longer and transferred more sperm to large females. As female size was positively correlated with fecundity, this suggests that males gain a selective advantage by investing more in large females. Given these findings, we consider how female mate preference for large male eyespan can be adaptive despite the lack of obvious direct benefits.